2020
DOI: 10.1038/s41598-020-60586-2
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Optimal Mass Transport with Lagrangian Workflow Reveals Advective and Diffusion Driven Solute Transport in the Glymphatic System

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, some studies 35–37 have questioned the role of advection and contended that diffusion plays the most important role in the transport of neurofluids 38–44 . One recent study 45,46 used mathematic modeling to suggest that both diffusion and advection are involved in fluid transport in the parenchyma. However, a review of such studies 47 concluded that there is a consensus that suggests diffusion is most likely the primary agent that drives fluid transport in the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies 35–37 have questioned the role of advection and contended that diffusion plays the most important role in the transport of neurofluids 38–44 . One recent study 45,46 used mathematic modeling to suggest that both diffusion and advection are involved in fluid transport in the parenchyma. However, a review of such studies 47 concluded that there is a consensus that suggests diffusion is most likely the primary agent that drives fluid transport in the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cluster analysis is performed on time-series signal data to show the speed of contrast agent uptake in different brain regions or the general direction of contrast agent movement (17,31,38). Optimal mass transport (OMT) modelling has emerged as an excellent tool for visualizing movement of intrathecal contrast agents through the brain (39). However, these semi-quantitative techniques do not permit the determination of the fundamental parameters characterizing molecular transport that are independent of experimental procedures and allow direct comparison with known diffusion rates.…”
Section: Introductionmentioning
confidence: 99%